STUDY OF CRUSTAL STRUCTURE OF THE FLORES ISLAND USING RECEIVER FUNCTION METHOD - Nanda Dewi Pamungkas Siwi; Ramadhan Priadi; Puji Ariyanto (Spektra: Jurnal Fisika dan Aplikasinya, 2022)
Flores is an island located in the north of the East Nusa Tenggara region. Formed as a consequence of very complex tectonic setting that might cause relatively high level of seismic in the region. This study aims to characterize the crust structure based on the S wave velocity model, the Vp/Vs ratio, and crustal thickness beneath the station on Flores Island. This study was using receiver function analysis method of teleseismic earthquake data with magnitude criteria ≥ 6 and epicenter distance 30⁰-90⁰. Seismic signal recorded on broadband stations three components. This study was using LBFI station. Velocity model of S wave and Vp/Vs ratio determined by using the non-linear Neighbourhood Algorithm (NA) inversion. Furthermore, the velocity and Vp/Vs ratio models will be used to obtain the depth of the migration process of the amplitude of the receiver function to depth. From the results of processing the depth of the Moho layer on the island of Flores under the LBFI station was identified as 41 km. The existence of the slab can be identified quite well that is at depth about 110 to 140 km.